Using the city: migrant spatial integration as urban practice - Buhr, Franz (2019)
This paper explores the idea of migrant spatial integration through an approach focused on urban praxis. Joining other contributions concerned with the continuing significance of place and locality for the study of migrant settlement, this paper examines migrants’ urban apprenticeship and how it shapes their usage of city space. Departing from the idea that to ‘integrate’ urban space involves being able to navigate it and being aware of its resources, I introduce an exploratory tool, which brings together processes normally kept apart in social scientific research, namely urban experience and migrant integration. Drawing from ethnographic interviews carried with migrants in Lisbon, Portugal, I argue that looking at migrants as skilful agents in the practice of city life may capture how the mechanics of migrant emplacement work in the context of urban diversity.